Occurrence of adults and biological aspects of Geniates borelli Camerano (Coleoptera, Scarabaeidae, Rutelinae) in Aquidauana, MS, Brazil - Rodrigues,Sergio Roberto (2012)
Occurrence of adults and biological aspects of Geniates borelli Camerano (Coleoptera, Scarabaeidae, Rutelinae) in Aquidauana, Mato Grosso do Sul, Brazil. Due to the importance of Geniates borelli Camerano as a pest in many crops, studies were developed at Universidade Estadual de Mato Grosso do Sul, Aquidauana campus, MS, Brazil. Adults were collected with a light trap from January 2006 to December 2007. 3,320 adults were collected, and the highest quantities were obtained in October 2006 and November 2007, with 1,548 and 802 adults recorded, respectively. Collected adults were kept in plastic containers with soil and Brachiaria decumbens seedlings for oviposition. 535 eggs measuring 2.30 × 1.60 mm were obtained. As the embryonic development progressed, eggs increased in size to 3.00 × 2.70 mm, and this change occurred between 6 and 10 days after oviposition. The embryonic period lasted 17.9 days. The first, second, and third instars lasted 37.6, 49.7, and 74 days, respectively. The prepupal stage lasted 65.9 days and the pupal stage lasted an average of 18.5 days. The biological cycle is completed in 315.8 days, which characterizes the species as univoltine. The average longevity of females was 35.4 days and 28.5 days for males.